2020
DOI: 10.1038/s41388-020-1184-9
|View full text |Cite
|
Sign up to set email alerts
|

Dual disruption of aldehyde dehydrogenases 1 and 3 promotes functional changes in the glutathione redox system and enhances chemosensitivity in nonsmall cell lung cancer

Abstract: Aldehyde dehydrogenases (ALDHs) are multifunctional enzymes that oxidize diverse endogenous and exogenous aldehydes. We conducted a meta-analysis based on The Cancer Genome Atlas and Gene Expression Omnibus data and detected genetic alterations in ALDH1A1, ALDH1A3, or ALDH3A1, 86% of which were gene amplification or mRNA upregulation, in 31% of nonsmall cell lung cancers (NSCLCs). The expression of these isoenzymes impacted chemoresistance and shortened survival times in patients. We hypothesized that these en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 50 publications
(79 reference statements)
0
31
0
Order By: Relevance
“…RRM2 was also proved to mediate multi-drug resistance in multiple malignant tumors (Shah et al, 2014 ; Chen et al, 2019b ). Furthermore, aldehyde dehydrogenases 1 and 3 (ALDH1A1 and ALDH3A1), which were well recognized to play functional roles in drug resistance of NSCLC (Rebollido-Rios et al, 2020 ), were also found overexpressed in PC9-Br ( Figures 4B,D ). Consistent with the resistance of PC9-Br to EGFR targeted TKIs, we found the expression of EGFR and p-EGFR were significantly reduced in PC9-Br compared to parental PC-9 ( Figures 4C,D ), which was regarded as an important mechanism of EGFR-TKI resistance in other EGFR-mutant NSCLC cell lines (Tabara et al, 2012 ; Nozaki et al, 2014 ; Xu et al, 2018 ).…”
Section: Resultsmentioning
confidence: 96%
“…RRM2 was also proved to mediate multi-drug resistance in multiple malignant tumors (Shah et al, 2014 ; Chen et al, 2019b ). Furthermore, aldehyde dehydrogenases 1 and 3 (ALDH1A1 and ALDH3A1), which were well recognized to play functional roles in drug resistance of NSCLC (Rebollido-Rios et al, 2020 ), were also found overexpressed in PC9-Br ( Figures 4B,D ). Consistent with the resistance of PC9-Br to EGFR targeted TKIs, we found the expression of EGFR and p-EGFR were significantly reduced in PC9-Br compared to parental PC-9 ( Figures 4C,D ), which was regarded as an important mechanism of EGFR-TKI resistance in other EGFR-mutant NSCLC cell lines (Tabara et al, 2012 ; Nozaki et al, 2014 ; Xu et al, 2018 ).…”
Section: Resultsmentioning
confidence: 96%
“…ALDH3A1 is a member of the aldehyde dehydrogenase (ALDH) superfamily, which plays a crucial role in the metabolism of diverse endogenous and exogenous aldehydes (Koppaka et al, 2012 ). With the capacity of medium-chain aliphatic and aromatic aldehyde metabolizing enzyme, ALDH3A1 is abundant in the upper respiratory tract, cornea, digestive tract, esophagus, and stomach and is reported to be highly expressed in non-small cell lung cancer (NSCLC) as a prognostic marker for patients with NSCLC (Pappa et al, 2003 ; Rebollido-Rios et al, 2020 ). Most studies on this gene have focused on its role in increasing the resistance of tumor cells to anticancer drugs (Koppaka et al, 2012 ), assisting ALDH2 in acetaldehyde and ethanol metabolism (Chen et al, 2015 ), and its high expression representing a poor clinical prognosis of cancer (Rebollido-Rios et al, 2020 ), as well as its function in protecting intraocular tissues from exposure to UV radiation and reactive oxygen species-induced damage (Chen et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we tested the efficacy of an inhibitor of ALDH1/3 (DIMATE). DIMATE has well-known antiproliferative effects in acute myleoid leukemia, non-small cell lung cancer (NSCLC), melanoma, and prostate cancer in vitro [ 26 , 48 , 49 , 50 ]. This inhibitor has been used as a monotherapy or combined with a chemotherapeutic agent inducing ROS production in NSCLC, with the aim of disrupting ROS balance in cells to induce death.…”
Section: Discussionmentioning
confidence: 99%
“…This inhibitor has been used as a monotherapy or combined with a chemotherapeutic agent inducing ROS production in NSCLC, with the aim of disrupting ROS balance in cells to induce death. The combination of DIMATE and CDDP in NSCLC has a synergistic effect on cell death in vitro and in vivo [ 26 ]. Here, we combined DIMATE with radiotherapy (X-rays).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation